Implementasi Sistem Pendidikan Islam Masa Dinasti Abbasiyah di Era Modern - Cindy Oktavia Dea Apriningrum; Erika Fauziah; May Nur Sihmawati (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2023)
Humans need education in order to have the knowladge and skills to live life. In Islamic education is very concerned, especially during the Abbasid dynasty. At that time the Abbasid dynasty brought Islam to the peak of its glory. In this period, Islam began to dominate all fields, both in terms of the economy, education and evan to the expansion of the territory on a large scale to mainland Europe. In the field of Islamic education, it is experiencing a golden peak or golden age where many books are currently being translated into Arabic. Baghdad was the capital during the reign of the Abbasid dynasty. In this city science is developing very rapidly. Along with the development of educational technology, it’s increasingly advanced, but many young people forget the teachings of Islamic education. The method used is literature review or library research by examining articles related to the discussions. During the Abbasid dynasty there were also many educational institutions that participated in helping the community in learning so that they could create extraordinary changes and advance civilization. The caliph also gave awards to scholars who succeeded in creating a masterpiece. It’s hoped that with the progress of science and technology, the implementation of Islamic education in the modern era will also shine.